Modifications to temperature-based estimates of consumptive water use by mountain meadows - Temple, Darcy G., author; Smith, Dan H., advisor (Colorado State University. Libraries, 2008)
Legal and engineering water communities in Colorado utilize the original Blaney-Criddle method to manage competing demands for water in mountain meadows, yet Blaney-Criddle underestimates in semi-arid, high-elevation environments. Blaney-Criddle consists of a consumptive use (CU) term, f, that is the product of mean monthly temperature, t, and percentage of daylight hours; and a crop coefficient, k, which accounts for crop variation and additional meteorologic effects. Low night temperatures at high elevations incorrectly weight f, and year-to-year variability among k values often results in significant variation between computed consumptive use and lysimeter measurements. Three modifications of the Blaney-Criddle temperature expression were tested against two existing temperature methods (Blaney-Criddle with conventional mean t, and Hargreaves) using lysimeter measurements from nine irrigated grass meadow sites in the upper Gunnison River basin (1999-2003). Use of two modified temperature expressions resulted in improved correlation of estimated Blaney-Criddle f with lysimeter CU. These improvements were similar to those observed when estimating with Hargreaves, which incorporates an additional term, Tdiff, the difference between maximum and minimum daily temperature. Climatological sources of variability in the crop coefficient, k, were also examined. The May-September crop coefficients k were better correlated with Tdiff (r = 0.28 to 0.54) than with mean t (r = 0.01 to 0.43). Specific regression equations based on Tdiff were used to develop crop coefficients from a dataset comprising the current study and three previous calibration studies in Colorado mountain meadows. Based on the standard error of estimate (SEE), estimates using the modeled coefficients more closely predicted CU than did estimates based on averages of locally calibrated k's (SEE difference of up to 5 mm mo-1). Correlations of solar radiation (Rs, the primary energy input to evapotranspiration) with alternative temperature expressions and Tdiff were improved over correlations of Rs with mean t, supporting the improved prediction performance of alternative temperature expressions and of the modeled k based on Tdiff. Those modifications can be applied successfully throughout Colorado mountain basins, and it is hoped that the same technique can be applied to other areas of the western U.S.
Keywords: Blaney-Criddle method; Colorado; consumptive water use; evapotranspiration; Hargreaves method; mountain meadows; hydrologic sciences; agriculture